Creatine serum is not as effective as creatine powder for improving cycle sprint performance in competitive male team-sport athletes - Gill, N. D.; Hall, R. D.; Blazevich, A. J. (The Journal of Strength and Conditioning Research, 2004)
This study examined the effects of supplementation with either creatine monohydrate powder in solution (CP) or a widely available creatine serum (CS) on performance in a repeated maximal sprint cycling test (10 × 6 seconds, 24-second passive rest between sprints). Using a randomized, double-blind, crossover design, 11 competitive male athletes supplemented with creatine in 2 forms according to the manufacturer's recommendations on 2 separate occasions. The 2 supplementation protocols were (a) 20 g·day-1 × 6 days of creatine powder in solution plus a placebo serum (CP) or (b) 5 ml·day-1 × 6 days of creatine serum plus a placebo powder (CS). Subjects completed 2 familiarization trials before the 6-day supplementation period. A repeated maximal sprint cycling test was performed prior to and immediately postsupplementation. A 7-week washout period separated the 2 supplementation protocols. Subjects' total work (9.6%) and peak power (3.4%) in the cycle sprint improved significantly (p < 0.05) after loading with CP, but there was little change after loading with CS. The present data support previous research findings showing an ergogenic effect of CP supplementation but indicate that supplementation with CS does not affect sprint cycling performance. Although the levels of creatine in each formulation were not determined, a substantial conversion of creatine into creatinine has been reported in many formulations and may explain the present findings.